Marketisation and privatisation in criminal justice - Albertson, Kevin 1963-; Corcoran, Mary; Phillips, Jake (Policy Press, 2020)
This collection offers a comprehensive review of the origins, scale and breadth of the privatisation and marketisation revolution across the criminal justice system. Leading academics and researchers assess the consequences of market-driven criminal justice in a wide range of contexts, from prison and probation to policing, migrant detention, rehabilitation and community programmes. Using economic, sociological and criminological perspectives, illuminated by accessible case studies, they consider the shifting roles and interactions of the public, private and voluntary sectors. As privatisation, outsourcing and the impact of market cultures spread further across the system, the authors look ahead to future developments and signpost the way to reform in a 'post-market' criminal justice sphere